Sosa's Way: Ernest Sosa interviewed by João Carlos Salles - Sosa, Ernest; Salles, João Carlos (Analytica - Revista de Filosofia, 2024)
Ernest Sosa is one of the most important contemporary philosophers. His work constitutes its own field of reflection that recently took the form of a theory of telic normativity in his Epistemic Explanations: A theory of telic normativity, and what it explains (Oxford: OUP, 2021). Telic normativity is inherent to actions, to attempts that characterize human performances, being telic because they are aimed at ends and often normative because we say they are better if successful and, therefore, if they reach their objective. It is also better for attempts to manifest competence and attain success through competence and not by chance. That is why we prefer persuasion to the use of force, an excellent diagnosis to mere guessing, the expert’s advice to the charlatan’s opinion. Also, we attribute merit to regular athletic performances rather than casual successes. After all, as Sosa reminds us, “to reach Larissa through ignorant luck is not to flourish.” The philosophical community still grasps all the subtleties his recent position implies, and Sosa has another step in turning his reflection into a Dawning Light Epistemology. This capacity to constantly improve his position is not surprising. Indeed, since 1964, Sosa’s presence in the epistemological field is the most relevant, both as a deep thinker whose work evolves and elaborates its identity amidst an intense dialogue and as an academic worker who deals with the complex activities related to the organization of the philosophical community. In this Interview, Sosa allows us to glimpse intricate aspects of his epistemology (e.g., epistemic modalities, philosophical methodology, and the Dawning) and exciting facts of his personal life and academic trajectory (e.g., people that contribute to his career and those he debated over the years). The interview is, per se, a clear example of his generosity, the richness of his trajectory, and the scope and profundity of his thoughts. His words, as we all can see, clearly illustrate a trajectory and thinking that opens us to philosophical flourishing.